Diagnostic uncertainty and insurance coverage in credence goods markets - Loukas Balafoutas; Helena Fornwagner; Rudolf Kerschbamer; Matthias Sutter; Maryna Tverdostup (Max Planck Institute for Research on Collective Goods, 2023)
In markets for credence goods - such as health care or repair services - fraudulent behavior by better informed experts is a common problem. Our model studies how four common features shape experts' provision behavior in credence goods markets: (i) diagnostic uncertainty of experts; (ii) insurance coverage of consumers; (iii) malpractice payments for treatment failure; and (vi) consumer-regarding preferences of experts. Diagnostic imprecision unambiguously leads to less efficient provision. Insurance coverage and malpractice payments have an ambiguous effect on efficient provision. The impact of consumer-regarding preferences on efficiency is positive without insurance but ambiguous in the presence of insurance.
hdl:21.11116/0000-000D-C219-C
Keywords: D82; G22; 330; Credence goods; diagnostic uncertainty; insurance coverage; social preferences